Implementasi Program Inklusi bagi Peserta Didik dengan Hambatan Fisik Motorik: Studi Kasus Penanganan oleh Guru Kelas di SDN 2 Kemiri - Ani Setyorini; Liftiah Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of an inclusive education program for students with physical motor impairments, focusing on the role of a classroom teacher at SDN 2 Kemiri, Indonesia. Using a qualitative case study approach, data were collected from February to April 2026 through participant observation, in-depth interviews with the classroom teacher (codenamed SE), and documentation of the student (codenamed INZ), who has locomotor disabilities. The study aims to describe the teacher’s strategies, challenges encountered, and the support system provided by the school principal as the policymaker at the school level. Results indicate that the classroom teacher implemented three main strategies: modification of learning media and classroom layout, individual assistance during specific subjects requiring fine motor skills, and regular collaboration with parents and the school principal. Key challenges included the teacher’s limited formal training in special education, inadequate physical infrastructure such as accessible ramps and restrooms, and time constraints for preparing individualized learning plans. Despite these obstacles, positive outcomes were observed in the student’s participation, learning motivation, and basic academic achievement. The study concludes that a committed classroom teacher can significantly enhance inclusive practices even when systemic support is limited. Recommendations include compulsory in-service training for all classroom teachers, provision of minimum accessibility standards in every school, and a more structured role for school principals in monitoring and evaluating inclusive programs. This research contributes to the growing body of knowledge on inclusive education in Indonesian elementary schools, particularly in non-urban settings.